EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) DAN IMPLIKASINYA TERHADAP KUALITAS PENDIDIKAN - Agus Susanto (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2022)
This research aims to describe the evaluation of Islamic religious education learning based on information and communication technology (ICT) and its implications for the quality of education. The development of the times can be marked by advances in science and advanced technology. Therefore, in the teaching and learning process it is also necessary to develop new ways of teaching. Among them is how to teach using information and communication technology (ICT/ICT). With the presence of ICT, Islamic Religious Education teachers are no longer focused on their role as teachers, but Islamic Religious Education teachers also have the task of learning and developing their resources by mastering scientific knowledge. Islamic Religious Education Teachers must be aware that ICT is also the most important tool in developing Islamic Religious Education learning. The research method used is descriptive qualitative by describing phenomena and existing literature. The results of the study show that ICT facilities in the world of education play an important role in overcoming the problems of limited educational facilities or facilities that support the teaching and learning process of Islamic Religious Education. The presence of technology in schools can improve the quality of Islamic Religious Education learning, because through information and communication technology (ICT) teaching creativity can be developed which is very helpful in the smoothness and success of the teaching and learning process.